2013
DOI: 10.1007/978-3-642-38833-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Agility and Discipline in a Medical Device Software Organisation

Abstract: Agile development techniques are becoming increasingly popular in the generic software development industry as they appear to offer solutions to the problems associated with following a plan-driven Software Development Life Cycle (SDLC). However, agile methods may not be suited to all industries or organisations. For agile methods to succeed, an organisation must be structured in a way to accommodate agile methods. Medical device software development organisations are bound by regulatory constraints and as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
1
11
0
3
Order By: Relevance
“…Additionally, few studies specifically emphasised the impact of agile adoption upon the company and the team culture [12].…”
Section: Use Of Agile In Highly Regulated Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, few studies specifically emphasised the impact of agile adoption upon the company and the team culture [12].…”
Section: Use Of Agile In Highly Regulated Environmentsmentioning
confidence: 99%
“…This created interest from the medical device community in relation to the suitability of agile for the development of regulatory compliant software. A working group was formed by the Association for the Advancement for Medical Instrumentation (AAMI) and they produced AAMI:TIR 45:2012 [11] which is an internationally accepted technical report outlining that "agile practices can be successfully adopted to develop regulatory compliant software" [12]. Agile software development literature reports "the promise of improved software quality and reduced delivery times" [13].…”
Section: Agile Software Developmentmentioning
confidence: 99%
“…However, due to successes reported within other domains from implementing agile practices, an international working group was set up to investigate if agile practices could fulfil the requirements of IEC 62304. The Association for the Advancement for Medical Instrumentation working group found that “agile practices can be successfully adopted to develop regulatory compliant software” and produced AAMI:TIR 45:2012, which is an internationally accepted technical report called “Guidance on the use of Agile practices in the development of medical device software.” AAMI:TIR 45 provides general guidelines on how agile methods may be used to satisfy IEC 62304. To obtain a suitable development life cycle for MMAs, we have compared various potential MD software development approaches before deciding to develop an MMA framework where agile practices are combined with MDevSPICE while observing the guidelines of AAMI:TIR 45.…”
Section: Approach Used To Understand the Needs For Mma Development Frmentioning
confidence: 99%
“…As this approach is not based on MDevSPICE there is an overhead on ensuring that all the regulatory practices are in place for each required standard together with the necessary documentation. Previous research on integrating agile practices into the V-model to streamline requirements changes found that this reduced the amount of rework required and helped deliver MD software in a more timely manner [24].…”
Section: Introducing Agile Practices Into the V-model Lifecycle (Nmentioning
confidence: 99%